Not All Abdomens Are the Same: A Comparison of Damage Control Surgery for Intra-abdominal Sepsis versus Trauma. Issue 5 (May 2016) - Smith, Jason W.; Nash, Nick; Procter, Levi; Benns, Matthew; Franklin, Glen A.; Miller, Keith; Harbrecht, Brian G.; Bernard, Andrew C.
Damage control surgery (DCS) was developed to manage exsanguinating trauma patients, but is increasingly applied to the management of peritoneal sepsis and abdominal catastrophes. Few manuscripts compare the outcomes of these surgeries on disparate patient populations. A multi-institutional three group propensity score matched case cohort study comparing penetrating trauma (PT-DCS), blunt trauma (BT-DCS), and intraperitoneal sepsis (IPS-DCS) was performed comparing patients treated with DSC between 2008 and 2013. Propensity scoring was performed using demographic and presenting physiologic data. Four hundred and twelve patients were treated with DCS across two institutions. Propensity matching for age, gender, and initial Acute Physiology and Chronic Health Evaluation II score 80 identified 80 patients per group for comparison. Rate of primary fascial closure was lowest in the IPS-DCS group, and highest in the penetrating trauma DCS group. Intra-abdominal complication rates were highest in the IPS-DCS group. IPS-DCS had increased time to definitive closure compared with the other two groups (RR 1.8; 1.3–2.2; P < 0.03). Mortality at 90 days was highest in the IPS-DCS group and patients whose definitive closure was delayed >eight days were more than twice the risk of death at 90 days across all groups. (RR 2.15; 1.2–3.5; P < 0.002). Expected outcomes after the use of DCS for trauma and emergency general surgery are quite different. Despite this difference, prompt abdominal closure at the earliest possible opportunity afforded the best outcome in patients managed via DCS.